Infak dan Kesehatan: Strategi Penyediaan Layanan Kesehatan bagi Masyarakat Marginal - Juvither Teguh Alfharizqi, Mochammad; Noer Destiana, Alifvia; Puspa Dewi, Ranti; Arwini Gunawan, Sandra; Rahmania Salsabila, Syifa; Friantoro, Dian (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
Infak or donation is an act of giving a portion of wealth or resources for the public benefit which is intended solely for the sake of Allah, without expecting any material return. It has the potential to address social injustice problem that occurs on marginalized communities, for example to solve healthcare disparities among communities due to financial constraints. This research aims to explore the strategies of infaq as an alternative funding source for the marginalized community using a literature review approach. The results of this study show that infaq has the potential to be an alternative source of funding for public health services. With an inclusive and sustainable funding strategy and mechanism, this idea can have implications for public awareness to maximize infaq management. A good infaq management strategy can expand access to fair and equitable health services, especially for marginalized communities.